On threshold effect of housing finance on shared prosperity: Evidence from sub‐Saharan Africa - (:unkn) unknown (My University, 2023)
Applying panel threshold regression technics along with alternative econometric investigation on a panel database of 48 sub-Saharan African (SSA) countries over the period 2000–2012, this paper analyzes the structure of housing finance in SSA countries and mainly verifies if there is a threshold effect on shared prosperity. Independently of the method used, our findings offer strong evidence of an inverted U-shaped relationship between housing finance and inequality. The current level of development of housing finance in SSA, which is at its very early stage, is not yet an effective tool for reducing economic inequality; however, beyond a given threshold, housing finance becomes effective in reducing inequality. Indeed, higher values of housing finance depth above a certain threshold of 6.35% reduce inequality, whereas values below 6.35% and very high values have no significant impact. In addition, there is a slightly positive relationship between housing finance and labor productivity growth in SSA. Results also show that the way housing finance impact inequality is highly dependent on their ability to implement effective crisis fight policies. Controlling for countries’ income levels, legal origin, and regional proximity revealed relative benchmarking, typology, and characteristics of SSA housing finance. These findings suggest some policies to stimulate the development of housing finance in SSA. As a bonus, this paper also highlights several other pillars that can be used to support shared prosperity in SSA.
Keywords: African Research